Design and locomotion control of a hydraulic lower extremity exoskeleton for mobility augmentation. (October 2017) - Kim, Hongchul; June Shin, Young; Kim, Jung
Highlights: System design and locomotion control are proposed for a hydraulic exoskeleton. For movement comfort, the wearer and exoskeleton motions are made to coincide. Locomotion control algorithms for stable normal walking are described. The effectiveness of locomotion control for the developed exoskeleton is verified. Abstract: In this paper, a system design and three locomotion control algorithms are proposed for a hydraulic lower extremity exoskeleton to enhance mobility and reduce muscle fatigue caused by backpack loads. The range of motion of the exoskeleton and the capacity of the hydraulic power unit, which generates the hydraulic flow and pressure, are determined by analysing human walking data obtained using a motion capture device and force plates. For movement comfort, the mechanical structure and the joints of the exoskeleton are designed such that the motion of the wearer coincides with that of the exoskeleton. In addition, locomotion control algorithms for stable normal walking are described; these algorithms enable dual-mode control and transition control. Dual-mode control is comprised of an active mode in the stance phase and a passive mode in the swing phase. In the active mode, the exoskeleton is controlled to track the motion of the wearer, and in the passive mode, its active joints work as passive joints by blocking the hydraulic power supply from the hydraulic power unit. Transition control, which consists of a torque-shaping method and a pre-transition algorithm, is adopted to improve locomotion responses during gait phase transition. Finally, to verify the effectiveness of the locomotion control algorithms and the developed hydraulic lower limb exoskeleton, walking experiments are performed on a treadmill, at a speed of 4 km/h, while carrying 45 kg backpack loads. The assistance effect of the exoskeleton is also validated by comparing the electromyography (EMG) signals of four selected muscles, with and without the exoskeleton, for single stance and level walking while carrying the same 45 kg backpack loads.